Analysis of the Effect of Selling Price on Sales Volume of Broiler Chickens (Case Study at Majene Central Market) - Asriani; Susanti, Irma; Agustina; Nuraliah, Siti; Khaliq, TD; Suhartina; Dahniar; Angka, Andi Werawe; Rohani, St (Tarjih : Agribusiness Development Journal, 2024)
The sales volume in broiler chicken marketing carried out by traders in the market can be influenced by many factors. One of the factors that can influence sales volume is the selling price of chickens, therefore this research aims to analyze the influence of selling prices on sales of broiler chickens in the Majene central market. This research was carried out from June to July 2023 at the Majene Central Market, with 10 broiler chicken traders as respondents.  The data obtained was processed using simple linear regression analysis. The results of the research show that the selling price has a significant effect on the sales volume of broiler chickens in Majene's central market with an influence of 60.2% and 39.8% is influenced by other factors, with the explanation that if the selling price of broiler chickens rises by one thousand rupiah, then the sales volume will decrease as many as 6 individuals. The novelty in this research is that there has been no similar research carried out in the Majene central market, so the results of this research can be a reference for traders in determining prices to maximize profits obtained.